PENGARUH MODEL SIKLUS BELAJAR 5E (Engagemant, Exploration, Explanation, Elaboration, Evaluation) TERHADAP KEMAMPUAN APLIKASI KONSEP SISWA PADA MATERI SISTEM SARAF - Andra Rian Mulyna; Tuti Kurniati; tri wahyu agustina (Jurnal BIOEDUIN : Program Studi Pendidikan Biologi, 2017)
This research supported by the problems emerging in class xi mia sman 27 bandung because less increasing study results in learning biology students. To overcome these problems by using a learning process implemented learning model  learning cycle5E. This study aimed to determine the effect of the  Learning Cycle 5E model of application of the concept of students' abilities in the material of the nervous system as well as knowing keterlaksanaan process of learning by using learning model 5E learning cycle on the material of the nervous system.The method used is Quasi-Experimental Design with a sample that is class I and class XI XI MIA MIA II the number of students in each class of 30 students. The sampling technique used was purposive sampling. Research instrument used was a set of tests and observation sheet. Analysis of study data including normality test, homogeneity test and test hypotheses.Results of analysis keterlaksanaan learning process by using the  learning cycle 5E model of the average values obtained 97.50% berkategorikan good enough for the activities of teachers and 96% berkategorikan good enough for the student activity. The results showed that the application of the concept of students' ability to use the learning cycle 5E learning model obtained an average value of 44.56 initial test, the final test of 72.17, NGain of 0.50 berkategorikan being an indicator of high concept application that indicator application of the material that has been learned within the family, school, community. Application of the concept of students' abilities without using 5E learning cycle model obtained an average value of 43.31 initial test, the final test 55.26, N 0.21 Gain berkategorikan-low, high-concept application indicators are indicators of the application of the material that has been studied in the environment family, school, community. Hypothesis test results at the end of the test Learning Cycle 5E learning model on the nervous system material obtained t 5.06> 1.69 ttable at significance level of 5%. Based on the results of this study concluded that there are significant learning model Learning Cycle 5E on the ability of the students expressed significant application of concepts and hypotheses accepted.